Supply Chain Management on the Production Process and Distribution Flows of the Superior Teak Seedlings Production - Muhammad Alkaff; Marimin Marimin; Yandra Arkeman; Sukardi Sukardi; Herry Purnomo (International Journal of Supply Chain Management, 2018)
Management of supply chain that interrelates and integrates both consumers and suppliers in a process to make a value of product or service for consumers is very importance and strategic as well. The research objective is to analyze and improve the sustainability performance of production process and distribution flow of the teak seedling production within its supply chain. This research used multiple dimensional analysis and value stream mapping to identify the sustainability performance and analytical network process to find the key factors that improve the SCM performance of superior teak production. The research found that 1) the Parameter influencing SCM is supplier and therefore it requires system improvement. The problem is that the delivery of materials purchased in Surabaya takes too long time before they are stored in the warehouse. Placing a purchase order long time beforehand may apparently solve the problem. But in fact, it creates another problem because the materials are not to be stored in the warehouse for a long time due to their short expiry date and due to the limited infrastructures like warehouse and roads. SCM values on the production system of superior teak seedling production of BPPT located in Jatisari area is 56.62 with a quite high category. Based on the leverage analysis, the most dominating SCM components are waiting factor at the value of 2.71; overproduction at 2.30 and inventory at 2.25, 2) Based on the ANP analysis, the research found a position map of SCM components at the stress value of 3.411% meaning that it is an Excellent model suitability while the index of fit (R) is at 94.673% meaning it meets the appropriateness. Transportation process consists of transportation of auxiliary material of seedling production, travel of seedlings from nurseries to adapting areas, and distribution of seedlings. Slow supply of consumables required for seedling production process due to long distance between the production areas and supplier sites will cause delayed delivery of goods particularly of those that are not scheduled because of special cases. Keywords: Supply Chain, ANP, Transportation, Distribution Flows, Superior Teak Seedlings